THE EFFECT OF SERVICE AND COSTUMERS LOYALTY ON COSTUMERS SATISFACTION OF ONLINE TRANSPORTATION (Study Case: Students of IIB Darmajaya for MAXIM Users) - Sefnia Amalia Putri; Lukman Hakim; NURUL ZARIRAH (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to determine the effect of service and costumers loyalty on costumers satisfaction. The scope of this study was students of IIB Darmajaya and user MAXIM application. This study used two variables. Service (X1) and Costumers Loyalty (X2) were dependent variables and Costumers Satisfaction (Y) was the independent variables. The research methods of this study used mix methods and the data for this study was able to be collected using questionnaire.Keyword:  Service, Costumers Loyalty, Costumers Satisfaction, MAXIM